Eight New Peptaibols from Sponge-Associated Trichoderma atroviride - Irina Panizel; Oded Yarden; Micha Ilan; Shmuel Carmeli (Marine Drugs, 2013)
Eight new and four known peptaibols were isolated from a strain of the fungus, Trichoderma atroviride (NF16), which was cultured from an Axinellid sponge collected from the East Mediterranean coast of Israel. The structures of the pure compounds were determined using HRMS, MS/MS and one- and two-dimensional NMR measurements. The isolated compounds belong to the trichorzianines, a family of 19-residue linear hydrophobic peptides containing a high proportion of α-aminoisobutyric acid (Aib), an acetylated N-terminus and a C-terminal amino alcohol. These new peptaibols exhibited antimicrobial activity against environmental bacteria isolated from the Mediterranean coast of Israel.